Multi-server conjunctive keyword searchable encryption scheme based on BDH problem - Yanhua LU; Youliang TIAN; Chen LIU (Dianxin kexue)
Searchable encryption is a cryptographic primitive that supports users to search for keywords on ciphertext.In view of the low efficiency of traditional single-server searchable encryption schemes,it was based on the advantages of identity management in certificate management.In the multi-serve environment,a bilinear mapping was used to construct an identity-based encryption scheme that supports conjunctive keyword search.In this scheme,the storage and query of the encrypted data were allocated to different servers,and the retrieval efficiency of the user storage and keyword was improved by cooperation.Re-use the encryption and search ability of the connection keywords by using the identity of multi-server and user.At the same time,combine with the searchable encryption method of conjunctive keyword,a new security model was constructed based on bilinear pairing.And under the bilinear Diffie-Hellman problem,the scheme satisfies the ciphertext indistinguishability under selected message attack.